Postponed healthcare in The Netherlands during the COVID-19 pandemic and its impact on self-reported health - Visscher, Kirsten; Kouwenberg, Lisanne H. J. A.; Oosterhoff, Marije; Rotteveel, Adriënne H.; de Wit, G. Ardine (Frontiers in Health Services, 2023)
Background Healthcare services have been seriously disrupted during the COVID-19 pandemic. The aim of this study was to examine the extent to which Dutch citizens have experienced postponed healthcare and how this affected their self-reported health. In addition, individual characteristics that were associated with experiencing postponed healthcare and with self-reported negative health effects were investigated. Methods An online survey about postponed healthcare and its consequences was developed, and sent out to participants of the Dutch LISS (Longitudinal Internet Studies for the Social Sciences) panel (n = 2.043). Data were collected in August 2022. Multivariable logistic regression analyses were carried out to explore characteristics associated with postponed care and self-reported negative health outcomes. Results Of the total population surveyed, 31% of the panel experienced postponed healthcare, either initiated by the healthcare provider (14%), on their own initiative (12%) or as a combination of both (5%). Postponed healthcare was associated with being female (OR = 1.61; 95% CI = 1.32; 1.96), presence of chronic diseases (OR = 1.55, 95% CI = 1.24; 1.95), high income (OR = 0.62, 95% CI = 0.48; 0.80) and worse self-reported health (poor vs. excellent OR = 2.88, 95% CI = 1.17; 7.11). Overall, 40% experienced temporary or permanent self-reported negative health effects due to postponed care. Negative health effects as a result of postponed care were associated with presence of chronic conditions and low income levels (p < 0.05). More respondents with worse self-reported health and foregone healthcare reported permanent health effects as compared to those with temporary health effects (p < 0.05). Discussion People with an impaired health status are most likely to experiencing postponed healthcare and negative health consequences as a result. Furthermore, those with negative health consequences decided to forego health by themselves more often. As part of long-term plans to maintain the accessibility of healthcare services, specific attention should be paid to reaching out to people with an impaired health status.